Hijacking PrPc-dependent signal transduction: when prions impair Aβ clearance - Hernandez-Rapp, Julia; Martin-Lannerée, Séverine; Hirsch, Théo Z.; Launay, Jean-Marie; Mouillet-Richard, Sophie (Frontiers in Aging Neuroscience, 2014)
The cellular prion protein PrPC is the normal counterpart of the scrapie prion protein PrPSc, the main component of the infectious agent of Transmissible Spongiform Encephalopathies. The recent discovery that PrPC can serve as a receptor for the amyloid Αβ peptide and relay its neurotoxicity is sparking renewed interest on this protein and its involvement in signal transduction processes. Disease-associated PrPSc shares with Αβ the ability to hijack PrPC-dependent signalling cascades, and thereby instigate pathogenic events. Among these is an impairment of Αβ clearance, uncovered in prion-infected neuronal cells. These findings add another facet to the intricate interplay between PrPC and Αβ. Here, we summarize the connection between PrP-mediated signalling and Αβ clearance and discuss its pathological implications.